Ezekiel and the Twelve: Similar Concerns as an Indication of a Shared Tradition? - Morgan, David M. (Bulletin for biblical research, 2010)
The book of Ezekiel is often divided into a tripartite literary structure. The temple building program in chaps. 40–48 has received not a little scholarly attention, but the preceding oracles in 33:1–39:29 and their function in the final form of the book have not received much consideration. Interestingly, the subject matter of the three sets of oracles in this section of Ezekiel corresponds with themes also evident in a synchronic reading of the Book of the Twelve. This essay examines the ideology for temple building made apparent through the literary structure of Ezekiel and the Twelve, and remarks are made regarding the significance of each "temple building story."